Nutrient analysis and antioxidant activity of dates powder (Pheonix daetylifera) - Nik Nur Syaza Nik Mansor Adbi (2022)
Dates (Pheonix dactyl( fera)have been known as a fruit that could give energy source to consumers due to their high sugar content especially in fasting month. Turning dates into powder form can help consumer to consume it for a little longer because of the short life of dates and it can be consumed as a sugar substitute. Therefore, the objective was to analyse nutrient content and antioxidant activity of dates powder by performing proximate analysis and determination of antioxidant activity by DPPH assay. The dates were dried by using oven drying method at 60°C temperature for 2 days to completely dry it and blend it to produce dates powder. The nutrient composition of date powder such as ash and moisture content, crude fat, crude protein and total soluble solids was determined and compared with sugarcane as the positive control. Next, the antioxidant activity of date powder was determined by using DPPH (standard 2,2-dipheny1-1- picrylhydrazyl) free radical scavenging assay and also was compared with sugarcane as the control. The nutrient content of date powder obtained were ash content (15.84 5.62%), moisture content (5.12 f 0.66%), crude protein (0.52 ± 0.17%) and zero crude fat content. The percentage total soluble solids (TSS) of date powder was 1.2 ± 0.05. Antioxidant activity analysis by using DPPH radical scavenging activity resulted that the date powder has higher antioxidant activity in every concentration (4, 8, 12, 16 and 20 mg/ml) compared to sugarcane sample. The inhibitory concentration 50 (IC50) values are a parameter to determine the antioxidant activity of the sample by comparing it with DPPH free radical assay (River-Cruz et al., 2020). The date powder sample has lower 1050 value which is 4.54 (mg/ml) compared to sugarcane sample which is 48.94 (mg/ml). The lower 1050 value means the higher antioxidant activity in the sample. In conclusion, date powder has higher nutrient content and antioxidant activity than sugarcane.